2013
DOI: 10.1074/jbc.m113.480178
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Protein Unfolding by the trans Ring of the GroEL-GroES Chaperonin Complex Stimulates Folding

Abstract: Background:Chaperonins like the GroEL-GroES complex facilitate protein folding in the cell. Results: Substrate proteins are captured by the open, trans ring of the GroEL-ATP-GroES complex and are partially unfolded. Conclusion: Maximally efficient folding requires repeated cycles of substrate protein unfolding by the GroEL-GroES complex. Significance: Establishing how substrate proteins are processed by chaperonins is essential for understanding how proteins fold inside cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
61
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 60 publications
3
61
0
Order By: Relevance
“…We also showed that GroEL assists Rubisco folding, at least in part, through two phases of multiple axis unfolding of the misfolded Rubisco monomer (21,23,36). In addition, we observed an encapsulation-dependent compaction of the Rubisco folding intermediate, hinting at the possibility of an active role for confinement inside the GroEL-GroES chamber (21,23,36). Work on Rubisco by others (37,39) also suggested that confinement of the Rubisco monomer alters the folding landscape of the protein.…”
mentioning
confidence: 54%
See 3 more Smart Citations
“…We also showed that GroEL assists Rubisco folding, at least in part, through two phases of multiple axis unfolding of the misfolded Rubisco monomer (21,23,36). In addition, we observed an encapsulation-dependent compaction of the Rubisco folding intermediate, hinting at the possibility of an active role for confinement inside the GroEL-GroES chamber (21,23,36). Work on Rubisco by others (37,39) also suggested that confinement of the Rubisco monomer alters the folding landscape of the protein.…”
mentioning
confidence: 54%
“…We previously demonstrated that Rubisco populates a kinetically trapped, misfolded monomer that is efficiently rescued by GroEL in the absence of aggregation (36). We also showed that GroEL assists Rubisco folding, at least in part, through two phases of multiple axis unfolding of the misfolded Rubisco monomer (21,23,36). In addition, we observed an encapsulation-dependent compaction of the Rubisco folding intermediate, hinting at the possibility of an active role for confinement inside the GroEL-GroES chamber (21,23,36).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Suffice to note that most (>99%) of the SP molecules that emerge from the cage with each turnover remain unfolded, still recognizable by GroEL. More importantly the rapid turnover of the SP by the symmetric GroEL:GroES 2 complex creates repeated opportunities for work to be done by the chaperonin machine by unfolding the SP (28)(29)(30) or its surrogates (31). As we have proposed in the iterative annealing mechanism, the rate of chaperonin-assisted protein folding is related to the number of iterations per unit time (32), in contrast to the Anfinsen cage model, which places a premium on extending the residence time of the encapsulated SP (5,6,22,23).…”
Section: On the Lifetime Of Anfinsen's Cage In The Presence Of Substratementioning
confidence: 99%